Dietary diversity and preferences among pregnant women and its association with anaemia - Twum-Dei, B.; Aryeetey, R.; Aduku, L.N.E. (Nutrition & Food Science, 2024)
Purpose – This study aims to assess the dietary choices of pregnant women and their relationship with their anaemia status. Design/methodology/approach – A mixed-method study comprising a survey and three focus group discussions (FGDs). The survey included 380 adult pregnant women with data collected on food choices, preferences and haemoglobin (Hb) status. Findings – More than 50% of women in the study had Hb concentration < 11.0 g/dl; mean Hb was 10.24 g/dl (SD ¼ 1.59). Univariate analysis was used to generate descriptive tabulations for socio-demographic characteristics of respondents, dietary choices for women and anaemia status. T-test and bivariate analysis between dietary diversity score of the women among the food groups consumed as well as their anaemia (Hb) status. This showed that women with high dietary diversity scores had improved Hb status (P ¼ 0.003), and those who consumed meat and fish, as well as dark leafy vegetables, had significantly high diversity scores (P ¼ 0.031 and P ¼ 0.049). Thematic analysis was used for analysing qualitative data. Research limitations/implications – The sample used in the study is unlikely to be fully representative of pregnant women in the Accra Metropolis. In addition, this study used a cross-sectional study design, making it difficult to establish causal associations between nutritional status and food choices of pregnant women. It does not also show variation in dietary practices by season of the year. The scope of the study did not allow for a detailed analysis, and this should be considered in future studies. Also, the study did not explore an obstetric factor like past bleeding history as well as the menstrual cycle of these pregnant women, as these factors are likely to interfere with the anaemia status of the pregnant women. Originality/value – This paper contributes significant value by specifically focusing on and clarifying the complex relationship between dietary choices and anaemia among pregnant women. It also provides insights into the distinct dietary patterns and preferences of pregnant women, which may be contributing to the high prevalence of anaemia. The results of the study can inform the development of localized, evidence-based interventions to address this critical public health concern, ultimately leading to improved maternal and foetal health outcomes.
Research Article
Keywords: Dietary diversity; Pregnancy; Anaemia; Dietary preferences